The effect of spin and friction on reaction forces in a soccer ball impact: A computational study - Mohd Hasnun Ariff, Hassan; Zahari, Taha (Centre for Advanced Research on Energy, 2018)
This study investigates the effect of spin and coefficient of friction on the reaction forces in a soccer ball impact. The analysis was conducted by means of finite element (FE) method. A validated soccer ball FE model was used. Angular ball velocity and the coefficient of friction between the ball and the impacted surface were varied in the simulations. The normal and friction forces were the output parameters of the simulations. The results show that the normal force is neither influenced by the coefficient of friction nor the angular velocity, while the friction force is influenced by all impact variables. This study shows that a soccer ball impact can be influenced by several external factors.